The Determinant of Consumer Surplus for Tourist in Belakang Padang Island, Batam City, Riau Islands Province - Jusman, Sani; Maryati, Sri (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
The study To analyze consumer surplus among tourists visiting Belakang Padang Island in Batam City, Riau Islands Province, and To analyze the factors influencing consumer surplus among tourists visiting Belakang Padang Island. This study employs samples survey data and secondary and Using a quantitative approach. The results reveal that Education does have a significant effect, Ages not significant, the environment and other alternative tourist destinations are significant, environment and other tourism alternatives are significant, and travel costs have no impact on ), and the findings of this study suggest that improvement of torists education, maintaining and upgrading environmental quality, improving tourist attractions, and improving local capacity and participation.